TINJAUAN TERHADAP KLAUSULA HARDSHIP DALAM HUKUM PERJANJIAN INDONESIA. - , Cinantya Prima Hapsari, Sularto, S.H., C.N., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to determine and analyze how Hardship clause in terms of contract law in force in Indonesia and restrictions on the application of Hardship clause in Indonesia. The method of writing in this thesis is a normative. The research focuses on the literature research which is relevant to the issues that have been formulated as the primary data. Data collection is done by tracking the books or library materials relevant to the issues under study, then reviewed and analyzed to look for problem solvers basis. Analysis of research conducted with qualitative methods, which classify and select the collected data depends on its quality and truth, then connected with theories derived from the literature research, and described systematically in order to obtain prescription in depth about the research study. Hardship clause viewed from Indonesian contract law can still be equated with the theory of relative force majeure, due to the difficulty of fulfilling achievement because there are events that prevent the debtor to do, the extent to which events unpredictable place and not under the control of the aggrieved party when closing the contract. Like hardship, in relative force majeure thus fulfilling achievement to be delayed and the contract is not broken. Hardship has not been set in the Indonesian Civil Code, but the basic provisions like the principle of freedom of contract and good faith can still be used as the basis for the parties in making and implementing the agreement. If there is a hardship case, Indonesian judge will use Indonesian law, which is provision about overmacht/ force majeure especially the theory of relative force majeure to solve the case.